X-ray Free Electron Lasers A Revolution in Structural Biology (Springer International Publishing, 2018)
The timely volume describes recent discoveries and method developments that have revolutionized Structural Biology with the advent of X-ray Free Electron Lasers. It provides, for the first time, a comprehensive examination of this cutting-edge technology. It discusses of-the-moment topics such as growth and detection of nanocrystals, Sample Delivery Techniques for serial femtosecond crystallography, data collection methods at XFELs, and more. This book aims to provide the readers with an overview of the new methods that have been recently developed as well as a prospective on new methods under development. It highlights the most important and novel Structural Discoveries made recently with XFELS, contextualized with a big-picture discussion of future developments.